P1455PRIORITIZATION BY MEDICAL DIRECTORS OF NUTRITIONAL PROTEIN VERSUS DIETARY PHOSPHORUS CONTROL IN HEMODIALYSIS PATIENTS: ASSOCIATION WITH MORTALITY IN THE DIALYSIS OUTCOMES AND PRACTICE PATTERNS STUDY (DOPPS). (6th June 2020) - Yamamoto, Suguru; Bieber, Brian; Komaba, Hirotaka; Kitabayashi, Hiroki; Nomura, Takanobu; Cases, Aleix; Combe, Christian; Pisoni, Ronald; Robinson, Bruce; Fukagawa, Masafumi
Abstract: Background and Aims: Patients undergoing dialysis for end-stage kidney disease (ESKD) have poorer nutritional status than the general population, and worse nutritional status is associated with poor clinical outcomes. Hyperphosphatemia is common in dialysis patients owing to abnormal mineral and bone metabolism. Nephrologists manage hyperphosphatemia by prescribing phosphate binders and/or recommending restriction of dietary protein intake; the latter may, however, adversely affect nutritional status. In this analysis, we address the hypothesis that, even in the presence of hyperphosphatemia, liberalizing dietary protein leads to better patient outcomes. Method: The analysis includes 11, 628 hemodialysis (HD) patients in 12 countries in DOPPS phase 4 (2009-2011), from 254 facilities where the medical director completed a survey reporting facility practices. Demographic data, comorbid conditions, laboratory values, and medications were abstracted from patient records. Mortality was assessed during study follow-up. The primary exposure variable was response to the following question: "For patients with serum albumin 3.0 g/dL and phosphate 6.0 mg/dL, do you typically recommend to (A) increase or (B) not change or decrease dietary protein intake?" The primary outcome was all-cause mortality, analyzed by Cox regression, stratified by country, accounting for facility clustering using robust sandwich covariance estimators, and adjusted for case-mix and laboratory values. Linear regression was used to model the associations between the exposure variable and intermediate nutritional markers including serum albumin, creatinine, and phosphorus. We used multiple imputation to replace missing values for model covariates. Results: Median follow-up was 1.4 years. In the case scenario, 91% of medical directors in North America recommended to increase protein intake compared to 58% in Europe (range=36-83% across 7 countries) and 56% in Japan (Figure). Advice to increase dietary protein intake was associated with 0.33 mg/dL higher serum creatinine levels (95% CI: 0.08-0.57) after adjustment for case mix, while clinically meaningful associations were not observed for serum albumin and phosphorus. Advice to increase dietary protein intake was weakly associated with lower mortality [HR (95% CI): 0.89 (0.77-1.03)]. The association with survival was stronger in patients with age 70+ years [HR (95% CI): 0.81(0.68-0.96), P=0.08 for interaction] and for those without diabetes [HR (95% CI): 0.81(0.66-0.98), P=0.20 for interaction] Conclusion: In this large international cohort study, the medical director's stated preference to recommend an increase in dietary protein intake for HD patients with low albumin and high phosphorus levels was most common in North America and was associated with higher patient serum creatinine levels and potentially lower all-cause mortality. Additional research into the possible benefits of protein intake liberalization for HD patients, even in the presence of hyperphosphatemia, is warranted. This abstract was directly supported by Kyowa Kirin Co., Ltd..